2020
DOI: 10.1080/1828051x.2020.1719910
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the trace minerals requirements for maintenance and growth of 35–50 kg Dorper × Hu crossbred ram lambs

Abstract: This study aimed at estimating the trace minerals net requirements for maintenance and growth of Dorper  Hu ram lambs using the comparative slaughter techniques in 35 lambs of 35-50 kg body weight (BW). Seven lambs were slaughtered at the initial BW (34.93 ± 0.37 kg) to determine the basal whole-body composition. Another seven lambs were fed ad libitum (AL) and then slaughtered when it reached 41.73 ± 0.53 kg BW. The remained 21 lambs were assigned into three treatment groups, seven animals each, and fed 100,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Therefore, the authors concluded that young lamb meat is more dietary and plays an important role in the human diet. Zhang et al (2020) studied the microelement requirements of lambs with a live weight of 35-50kg. It was noted that the need for manganese, iron, zinc, and copper in lambs with a live weight 35kg is 0.86, 70.41, 33.46, and 4.31mg/mL, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the authors concluded that young lamb meat is more dietary and plays an important role in the human diet. Zhang et al (2020) studied the microelement requirements of lambs with a live weight of 35-50kg. It was noted that the need for manganese, iron, zinc, and copper in lambs with a live weight 35kg is 0.86, 70.41, 33.46, and 4.31mg/mL, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The export of meat products from many countries is decreasing due to the pollution of the environment, feed, and water, as well as the higher-than-normal level of chemical elements in meat products (Kasap et al 2017;Xing et al 2019). The research has determined it conducted so far that the amount of some elements in the meat and organs of slaughtered animals is much higher than the physiological norm (de Arujo et al 2017;Schweinzer et al 2017;Egigba et al 2018;Zhang et al 2020;Derar et al 2022). The amount of chemical elements in the tissues of animals varies depending on their age, sex, and type of tissue (Johnson et al 1995).…”
Section: Introductionmentioning
confidence: 99%